Physicochemical properties and acceptability of three formulations containing fava bean, quinoa and corn flour extrudates - Velásquez-Barreto, Frank F.; Ramirez-Tixe, Edson E.; Salazar-Irrazabal, Mariana D.; Salazar-Silvestre, Elias (Revista de Ciencias Agrícolas, 2020)
Andean grains, widely distributed in the high areas of the Andean Highlands, can help to reduce malnutrition owing to their high content of protein and balance of essential amino acids. Recently, their consumption has changed as they are increasingly used for instant food mixtures. However, a better design and formulation are necessary to maintain Andean grains’ nutritional value and characteristics. In this study, we evaluated the physicochemical properties and acceptability of three formulations containing extruded corn (Zea mays L.), fava bean (Vicia faba L.), and quinoa (Chenopodium quinoa Willd) flours. Grain samples were collected from Choclococha, Acobamba, Huancavelica, Peru, and extruded at 95°C. Subsequently, three flour formulations were prepared. The formulation comprising 30% fava bean flour, 58% quinoa flour, and 12% corn flour consisted of 18.64% protein, 4.87% fat, 8.4% humidity, 2.99% ash, and 62.44% carbohydrates. This formulation with the highest quinoa flour content presented the highest acceptability in terms of color odor and flavor, and the highest protein content and digestibility (72.6%) of all analyzed formulations. Thermal analysis and pasting testing indicated that the formulation with the highest acceptability did not contain native starch; moreover, the proteins in this formulation were denatured.